Penguatan Identitas Lingkungan sebagai Media Pendidikan Masyarakat Melalui Program Kkn Berbasis Participatory Action Research - Fathullah, Amal; Reza Wardana; Muhammad Iqbal Afifbry; Muhammed Jamiel Husein; Ricky Fernando (Jurnal Dedikasi Pengabdian Pendidikan, 2026)
This community service activity aims to strengthen environmental identity while utilizing it as a medium for community education through a Kuliah Kerja Nyata (KKN) program. The activity was conducted by students of Universitas Islam Negeri Antasari in Sungai Lakum Village, Kertak Hanyar District, Banjar Regency, South Kalimantan, during the period of May–June, 2025. The method employed was Participatory Action Research (PAR) using a qualitative descriptive approach that positioned community members as active learners throughout all stages of the program, including problem identification, planning, implementation, and evaluation. The program focused on organizing environmental identity through the reinstallation of neighborhood head signboards and the creation of alley nameplates. The results indicate improved clarity of territorial identity, easier access to administrative services, and increased community awareness regarding environmental order, civic participation, and collective responsibility. The discussion highlights that the PAR-based KKN program not only produced tangible physical outcomes but also functioned as an effective form of non-formal community education, fostering social literacy and contextual learning based on real community needs.